Hubungan Minat Berwirausaha Bidang Busana dengan Prestasi Belajar Kewirausahaan Siswa Kelas XII Tata Busana SMKN 1 Wadaslintang Tahun Ajaran 2021/2022 - Indirasari, Iva Maya; Endarwati, Nanik (Universitas Pendidikan Indonesia Kampus Serang, 2022)
This study aimed to (1) describe the interest in entrepreneurship in the field of clothing, (2) to find out the description of the student achievement in entrepreneurship, and (3) to know the relationship between interest in entrepreneurship in the field of clothing and entrepreneurial learning achievements in students of the State of Vocational School 1 Wadaslintang, the Department of Fashion, Class XII for the 2021/2022 Academic Year. This type of research was a quantitative correlational type. To collect data, the authors used a questionnaire method and documentation. In this study, the documentation method was used as a complementary method to obtain data on the number of students at the Department of Fashion, Class XII, for the 2021/2022 academic year and odd semester report cards. The techniques used to analyze the data include descriptive analysis and correlational analysis. The results showed that students of the Fashion Design Department of Class XII in the odd semester were interested in entrepreneurship in the high category with a frequency of 50%. The entrepreneurial learning achievements were included in the moderate category with a relative frequency of 68.18%. The entrepreneurial learning achievements of most students majoring in Class Fashion XII Odd Semester were in the sufficient category. The significance value of the correlation that robtained value was higher than rtable, which is 0,576 0,244. It is proven that there was a positive and significant relationship between entrepreneurial interest and entrepreneurship learning achievement of Class XII students of the Department of Fashion Design Odd Semester at the State of Vocational School 1 Wadaslintang.